2015
DOI: 10.1097/igc.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin Is a Safe Alternative Option for Patients With Recurrent Gynecologic Cancers After Hypersensitivity Reaction to Carboplatin

Abstract: Objective The aim of this study was to determine the tolerability and efficacy of oxaliplatin in patientswith recurrent gynecologic malignancies after carboplatin hypersensitivity reactions in comparison with conventionally used cisplatin. Methods Forty-six patients were treated with platinum-based chemotherapy from 2006 to 2011 and developed hypersensitivity reactions to carboplatin. Oxaliplatin was administered to 27 patients; 19 patients received cisplatin. Clinicopathologic variables, toxicity, and time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
10
0
2
Order By: Relevance
“…Although a recent study from Nonna et al found that for patients with carboplatin induced hypersensitivity reaction, the use of oxaliplatin maybe a safer alternative [ 29 ], patients should be carefully monitored for signs and symptoms of anaphylaxis with any platinum-based chemotherapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent study from Nonna et al found that for patients with carboplatin induced hypersensitivity reaction, the use of oxaliplatin maybe a safer alternative [ 29 ], patients should be carefully monitored for signs and symptoms of anaphylaxis with any platinum-based chemotherapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Third, development of predictive biomarkers of actual drug response must be completed to allow for individualized therapeutic regimens. Platinum chemistry has been continuously refined over the last few decades resulting in multiple, clinically-approved derivatives with variable toxicity profiles and pharmacokinetics [ 10 , 14 , 42 ]. The continued development of newer agents is likely to further increase the availability of Pt agents for improved therapeutic regimens [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disease response (partial or complete) was observed in 43.2% of patients and 36.8% of responders who had a prior platinum hypersensitivity reaction and were not candidates for other platinum-containing regimens. Another recent study by Kolomeyevskaya et al explored the tolerability and efficacy of oxaliplatin in recurrent gynecologic malignancies setting after carboplatin hypersensitivity in comparison with cisplatin [64]. Forty-six patients with ovarian, endometrial and cervical cancers who developed hypersensitivity reaction to carboplatin were retrospectively analyzed.…”
Section: Platinum Agent Hypersensitivitymentioning
confidence: 99%